PENANAMAN NILAI KECERDASAN EMOSIONAL SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT ACHIEVEMENT DIVISION PADA KELAS VI MIN KOTA BIMA - Nurhidaya; Syahru Ramadhan; Nurdiniawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the era of globalization, emotional intelligence (EQ) has become one of the key factors in supporting student development, both in school environments and in their social lives. This study aims to identify the implementation of emotional intelligence value development through the cooperative learning model of Student Teams Achievement Division (STAD) in sixth-grade students at MIN Kota Bima. This research employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. The data sources consist of primary sources, including the quality development coordinator, homeroom teachers, and sixth-grade students at MIN Kota Bima, as well as secondary sources used as supporting materials. The findings indicate that the application of the STAD cooperative learning model has a positive impact on shaping students’ emotional intelligence. Teachers play an active role as facilitators by implementing appropriate and structured learning steps, enabling students to collaborate, understand their own emotions and those of others, and build strong social skills.